2007
DOI: 10.1107/s0021889807007637
|View full text |Cite
|
Sign up to set email alerts
|

Extending the charge-flipping method towards structure solution from incomplete data sets

Abstract: The charge-flipping method tends to fail if applied to an incomplete diffraction data set. The reason is artifacts induced in the density maps by Fourier transforming the data. It is shown that the missing data can be sufficiently well approximated on the basis of the Patterson map of the unknown structure optimized by the maximum entropy method (MEM). Structures that could not be solved by the original charge-flipping algorithm can be solved by the proposed method. The method has been tested on experimental d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…The quality of the final electron-density maps was checked by calculating the number of peaks that lie less than 0.55 Å from the correct atomic positions. As expected, Palatinus et al (2007) found that charge-flipping is more efficient for inorganic than organic structures.…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…The quality of the final electron-density maps was checked by calculating the number of peaks that lie less than 0.55 Å from the correct atomic positions. As expected, Palatinus et al (2007) found that charge-flipping is more efficient for inorganic than organic structures.…”
Section: Introductionsupporting
confidence: 75%
“…Thus, solving these structures at RES ' 1.8 Å is beyond the limits of the present state of the art. Similar difficulties were described in a recent paper (Palatinus et al, 2007), where the charge-flipping method was tested versus incomplete data sets; three triclinic test structures, one inorganic and two organic, were used. Incomplete data were artificially created according to different criteria: upper resolution limit, lower resolution limit, randomly omitted reflections or missing cone.…”
Section: Introductionmentioning
confidence: 99%
“…The most important experimental parameters are listed in Table S1. The structure solution was performed ab initio with the charge flipping algorithm 3335 implemented in the program Superflip 36 in Jana2006 37 using the kinematic approximation. A complete structural model with was found in the monoclinic SSG with and .…”
Section: Resultsmentioning
confidence: 99%
“…SADABS was used for applying the absorption correction . The crystal structure was solved using the program Superflip and refined by using the program JANA2006 . Refinement of anisotropic thermal parameters was made for all atoms.…”
Section: Methodsmentioning
confidence: 99%